2018
DOI: 10.1021/acs.jpcc.8b01432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecule–Surface and Molecule–Molecule Interactions on Two-Dimensional Patterns Formed by Functionalized Aromatic Molecules

Abstract: Molecules self-assemble on surfaces forming a variety of patterns that depend on the relative strength between the intermolecular and molecule-surface interactions. In this study, the effect of the physisorption/chemisorption interplay on self-assembly is investigated using Monte Carlo simulations. The molecules are modelled as hexagonal tiles capable of assuming two distinct adsorption states, with different diffusion properties, on a hexagonal lattice. The self-assembled structures that emerge by tuning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…We start by studying the adsorption of one monolayer of hexachlorobenzene on Pt(111) (see Figure a). This system was selected in the current study since previous experimental work has demonstrated the feasibility of forming a self-assembled monolayer of benzene derivative, including C 6 Cl 6 , on a metal surface. Theoretically, the Monte Carlo simulations have also predicted that a self-assembled monolayer of hexachlorobenzene (C 6 Cl 6 ) would form at 270 K on the Pt(111) surface. , The adsorption configuration of C 6 Cl 6 adsorbed on the Pt(111) surface, which presents a four-layer slab with the (3 × 3) unit cell, was calculated by the dispersion-inclusive DFT + vdW surf method along with the PBE exchange–correlation functionals. , Here, we investigate four high-symmetry adsorption geometries (atop, bridge, fcc, and hcp) with two orientations (0 and 30°) for hexachlorobenzene on the Pt(111) surface. We found that bri30° is the most stable adsorption geometry (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We start by studying the adsorption of one monolayer of hexachlorobenzene on Pt(111) (see Figure a). This system was selected in the current study since previous experimental work has demonstrated the feasibility of forming a self-assembled monolayer of benzene derivative, including C 6 Cl 6 , on a metal surface. Theoretically, the Monte Carlo simulations have also predicted that a self-assembled monolayer of hexachlorobenzene (C 6 Cl 6 ) would form at 270 K on the Pt(111) surface. , The adsorption configuration of C 6 Cl 6 adsorbed on the Pt(111) surface, which presents a four-layer slab with the (3 × 3) unit cell, was calculated by the dispersion-inclusive DFT + vdW surf method along with the PBE exchange–correlation functionals. , Here, we investigate four high-symmetry adsorption geometries (atop, bridge, fcc, and hcp) with two orientations (0 and 30°) for hexachlorobenzene on the Pt(111) surface. We found that bri30° is the most stable adsorption geometry (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, many studies apply simplifications at this juncture. For example, they perform Monte Carlo simulations on predefined monomer adsorption grids or employ machine-learning on coarse-grained models assembled from single-molecule adsorption data. , …”
Section: Introductionmentioning
confidence: 99%
“…One useful method to reduce the experimental efforts mentioned above are the computer simulations in which model parameters can be changed in a quick and easy way . This refers especially to the intrinsic properties of the building block, including its shape, size and distribution of interaction centers.…”
Section: Introductionmentioning
confidence: 99%
“…One useful method to reduce the experimental efforts mentioned above are the computer simulations in which model parameters can be changed in a quick and easy way. [15][16][17][18][19][20][21] This refers especially to the intrinsic properties of the building block, including its shape, size and distribution of interaction centers. Using the simplified coarse grained modeling, these parameters can be readily adjusted to model the 2D self-assembly of a given tecton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation